Estado e direito em Hans Kelsen e Herman Dooyeweerd - Paz, Anderson Barbosa (2024)
Introduction: Hans Kelsen (1881-1973), an Austrian legal positivist, and Herman Dooyeweerd (1894-1977), a Dutch legal philosopher, were contemporary thinkers who witnessed the rise of totalitarian power of the State expressed through legal norms. Both were concerned with discussing the relationship between the State and law, but diverged in the formulation of their legal philosophies: Kelsen advocated a conception in which the State became the embodiment of legal order, whereas Dooyeweerd distinguished law from the structure of the State. Objective: to analyze the theoretical commitments and the political-legal problems of Hans Kelsen's thought from the philosophy of Herman Dooyeweerd. Problematics: 1) Is the relationship between State and law in Hans Kelsen incapable of protecting civil society and individuals from the power of the State, as asserted by natural law theorists?; 2) Every philosophy that postulates normative principles limiting the legal production is an atemporal metaphysics that results in an anti-pluralist political conception, as argued by Hans Kelsen?. Hypotheses: 1) Natural law theorists are correct in asserting that Kelsen's Pure Theory of Law enables unlimited power to the State in face of civil society, lacking theoretical support for its protection; 2) Kelsen is mistaken in understanding that any philosophy positing limiting normative principles on legal production is an atemporal metaphysics resulting in an anti-pluralist political conception. Research justifications: 1) Analyzes, from the Dooyeweerdian transcendental critique, whether the commitments assumed by Kelsen regarding reality led him to a reductionist theory capable of leaving society unprotected before the power of the State; 2) Investigates whether Dooyeweerd's theory has the capacity to overcome both natural law and legal positivism. Results: 1) As natural law theorists claim, Kelsen's political and legal perspective, which reduces law to the logical aspect and delegates discussions of justice to the political sphere, does not provide society with legal protection before the normative power of the State; 2) The Dooyeweerdian political-legal conception demonstrates the possibility of a philosophy that finds limiting principles for legal production in the order of reality and acknowledges social plurality due to the openness of historical experience. Conclusion: Deeply polarized democratic societies need to discover objectively arranged norms in reality capable of generating political consensus and legitimate positivization, not through an atemporal metaphysics or the imposing will of an elite, but through the recognition that there is an order capable of generating more benefits for the common good.